Fungi of Raffaelea genus ( Ascomycota : Ophiostomatales ) associated to Platypus Cylindrus ( Coleoptera : Platypodidae ) in Portugal (Revista de Ciências Agrárias, 2008)
In the study of the fungi associated to Platypus cylindrus, several fungi were isolated from the insect and its galleries in cork oak, among which three species of Raffaelea. Morphological and cultural characteristics, sensitivity to cycloheximide and genetic variability had been evaluated in a set of isolates of this genus. On this basis R. ambrosiae and R. montetyi were identified and a third taxon segregated witch differs in morphological and molecular characteristics from the previous ones. In this work we present and discuss the parameters that allow the identification of specimens of the three taxa. The role that those ambrosia fungi can have in the cork oak decline is also discussed taking into account that Ophiostomatales fungi are pathogens of great importance in trees, namely in species of the genus Quercus.

FUNGI ASSOCIATED TO PLATYPUS CYLINDRUS FAB . ( COLEOPTERA : PLATYPODIDAE ) IN CORK OAK (Revista de Ciências Agrarias, 1996)
Platypus cylindrus is a pest that since the 80s of the last century has been considered a cork oak mortality agent in Portugal. It is an ambrosia beetle that establishes complex symbioses with fungi whose role in the insect-fungus-host interaction has not been completely clarified. In order to characterize P. cylindrus associated micoflora in Portugal, fungi were isolated from different beetle organs and from its galleries in cork oak trees. Fungi of the genera Acremonium, Aspergillus, Beauveria, Botrytis, Chaetomium, Fusarium, Geotrichum, Gliocladium, Nodulisporium, Paecilomyces, Penicillium, Raffaelea, Scytalidium, Trichoderma and of the order Mucorales were identified. An actinomycete of the genus Streptomyces was also identified. Some of these genera were related for the first time to this interaction. In the present work the isolated fungi are characterized and their contribution for beetle population establishment and tree weakness is discussed.